2021
DOI: 10.1111/sms.14068
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in sprinting: An insight into sub‐10 and sub‐11 s men and women sprinters

Abstract: We assessed sprint mechanical asymmetry in world‐class competitors and evaluated whether inter‐limb sex‐based differences in sprinting mechanics exist. The eight finalists in the men's and women's 100 m events at the 2017 IAAF World Championships were studied. Five high‐speed cameras (150 Hz) were used to capture two consecutive steps of the whole body between 47.0 m and 55.5 m from the start, while four additional cameras (250 Hz) focussed on the lower extremities. A total of 33 spatio‐temporal, touchdown and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
(40 reference statements)
2
14
1
Order By: Relevance
“…Based on the current results, this is more important for men, and training such muscle groups is required, as the same knee angle at TO post was more flexed in men than women (Table 1, p = 0.003). Unlike flat sprinting where following TD both men and women encounter a knee depression of ∼17 • (Bissas et al, 2018a(Bissas et al, ,b, 2022, before their knee returns to TD levels (∼154 • ) to support the take-off of the whole body, in hurdling as our data indicates, the depression during landing following the hurdle clearance is not reversible. As a result of this, the knee angle at TO following landing corresponds for most athletes to the point of maximum knee flexion.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Based on the current results, this is more important for men, and training such muscle groups is required, as the same knee angle at TO post was more flexed in men than women (Table 1, p = 0.003). Unlike flat sprinting where following TD both men and women encounter a knee depression of ∼17 • (Bissas et al, 2018a(Bissas et al, ,b, 2022, before their knee returns to TD levels (∼154 • ) to support the take-off of the whole body, in hurdling as our data indicates, the depression during landing following the hurdle clearance is not reversible. As a result of this, the knee angle at TO following landing corresponds for most athletes to the point of maximum knee flexion.…”
Section: Discussioncontrasting
confidence: 51%
“…The Direct Linear Transformation algorithm (Abdel-Aziz et al, 2015) was used to reconstruct the three-dimensional coordinates from individual camera's x-and y-image coordinates. The reliability of this digitizing process has been described in previous studies using the same methodological approach (including same operator) (Bezodis et al, 2019;Bissas et al, 2022). In addition, as timeseries data are being compared here, one joint angle (lead leg knee angle) for a randomly selected athlete was digitized throughout the entire analyzed phase on two occasions separated by a 48h interval.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, horizontal force production variables displayed the largest inter-limb differences (Figure 4), suggesting that a more pronounced forward-oriented asymmetrical response is a biomechanical trait of repeated treadmill sprints. Although not a universal finding [24], similar observations have been made for single [25] and multiple 'all out' running bouts [8,22]. Previously, Bissas et al [25] observed considerable variability in mechanical variables among the finalists of the men's and women's 100 m events during the 2017 IAAF World Championship.…”
Section: Sa Scores Are Metric-dependentmentioning
confidence: 53%
“…A plethora of information exists on the running requirements (i.e. distances, velocities) of EPL players but very limited information exists on player's running styles and interlimb asymmetries despite similar research in other sporting populations (Tucker and Hanley, 2020 ; Bissas et al, 2022 ). In terms of measurements which relate to kicking, it is not surprising that there exists an abundance of information on the knee extensor and flexor strength given the reported links with hamstring strain injuries (Lee et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%